-3y=x-6

Divide each term in -3y=x-6 by -3.

-3y-3=x-3+-6-3

Cancel the common factor of -3.

Cancel the common factor.

-3y-3=x-3+-6-3

Divide y by 1.

y=x-3+-6-3

y=x-3+-6-3

Simplify each term.

Move the negative in front of the fraction.

y=-x3+-6-3

Divide -6 by -3.

y=-x3+2

y=-x3+2

y=-x3+2

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Find the values of m and b using the form y=mx+b.

m=-13

b=2

The slope of the line is the value of m, and the y-intercept is the value of b.

Slope: -13

y-intercept: 2

Slope: -13

y-intercept: 2

Choose 0 to substitute in for x to find the ordered pair.

Replace the variable x with 0 in the expression.

f(0)=-03+2

Simplify the result.

Simplify each term.

Divide 0 by 3.

f(0)=-0+2

Multiply -1 by 0.

f(0)=0+2

f(0)=0+2

Add 0 and 2.

f(0)=2

The final answer is 2.

2

2

The y value at x=0 is 2.

y=2

y=2

Choose 3 to substitute in for x to find the ordered pair.

Replace the variable x with 3 in the expression.

f(3)=-33+2

Simplify the result.

Simplify each term.

Divide 3 by 3.

f(3)=-1⋅1+2

Multiply -1 by 1.

f(3)=-1+2

f(3)=-1+2

Add -1 and 2.

f(3)=1

The final answer is 1.

1

1

The y value at x=3 is 1.

y=1

y=1

Create a table of the x and y values.

xy0231

xy0231

Graph the line using the slope and the y-intercept, or the points.

Slope: -13

y-intercept: 2

xy0231

Graph -3y=x-6